Co-expression patterns of cancer associated fibroblast markers reveal distinct subgroups related to patient survival in oropharyngeal squamous cell carcinoma - Lyu, Su Ir; Johannsen, Jannik; Simon, Adrian Georg; Knipper, Karl; Wuerdemann, Nora; Sharma, Shachi Jenny; Thelen, Martin; Hansen, Kevin Karl; Fretter, Caroline; Klasen, Charlotte; Esser, Julia; Suchan, Malte Christian; et al. (Frontiers in Cell and Developmental Biology, 2024)
Background: The incidence of oropharyngeal squamous cell carcinoma (OPSCC) is rapidly increasing in high income countries due to its association with persistent high-risk human papilloma virus (HPV) infection. Recent scientific advances have highlighted the importance of the tumor microenvironment in OPSCC. In this study, including 216 OPSCC patients, we analyze the composition of four established markers of cancer associated fibroblasts (CAFs) in the context of intratumoral CD8 T-cell infiltration. Methods: Immunohistochemical staining for fibroblast activation protein (FAP), platelet-derived growth factor receptor beta (PDGFRb), periostin, alpha smooth muscle actin (α-SMA) and CD8 were analyzed digitally and their association with survival, tumor-and patient characteristics was assessed. Results: Co-expression of CAF markers was frequent but not associated with HPV status. FAP high and PDGFRb high expression were associated with increased CD8 T-cell infiltration. Low expression of PDGFRb improved patient survival in female patients but not in male patients. We identified PDGFRb low periostin low α-SMA low status as an independent predictor of improved survival (hazard ratio 0.377, p=0.006). Conclusions: These findings elucidate the co-expression of four established CAF markers in OPSCC and underscore their association with T-cell infiltration and patient survival. Future analyses of CAF subgroups in OPSCC may enable the development of individualized therapies.